Novel red fluorescence protein based microplate assay for drug screening against dormant mycobacterium tuberculosis by using paraffin - Yeware, Amar; Sarkar, Dhiman (Tuberculosis, 2018)
The hypoxia model of dormancy is widely used in drug screening programs to identify novel inhibitors against latent Mycobacterium tuberculosis disease. In earlier reported microplate assays, hypoxia was maintained by either sealing the microplate or shifting in an anaerobic chamber to develop dormant phenotype. In these assays, inhibitors were added during inoculation, which mainly represents the active stage inhibitors instead of the dormant ones. Herein, the culture was covered with paraffin to develop hypoxia condition and consequently providing the advantage of adding compounds at any stage during incubation of 96-well plate. The stable expression of the red fluorescent protein in the bacilli under both actively growing as well as dormant conditions also facilitate the reliable estimation of growth and inhibition kinetics of bacilli in medium. Furthermore, S/N ratio and Z' factor of this assay were found to be > 27 and 0.91-0.94 respectively, which confirm the robustness of the protocol. This newly developed drug-screening assay offers an easy, inexpensive, safe and high throughput-screening tool to search novel antitubercular inhibitors against both active and dormant bacilli. The red fluorescent H37Ra strain is a suitable surrogate for the more virulent H37Rv strain, and thus this effort will help in combating latent tuberculosis.